Diagnostics of Children with Special Needs Readiness to School - Chaharna, Svitlana (Psychological Prospects Journal, 2015)
The article deals with the problem of psychological readiness of children with special needs to school studies. It is indicated that readiness to school is multidimensional phenomenon that includes appropriate psychological, physiological, physical and mental characteristics of the children’s development and enables  systematic schooling. Theoretical generalization of the study affords to single out a number of problems focusing on psychological readiness for school, level of cognitive activity development, social-communication skills, emotional-volitional, learning motivation, relevant knowledge and view of the outside world. Analysis of general and specialized literature has shown that over the past decade national psychology gained much experience in diagnosing readiness for school, and most urgently the issue  arises in the case of its application to children who were developing in adverse conditions, particularly in terms of auditory deprivation. The use of the following techniques «Development of fine motor skills», «Development of spatial  orientation,motor  coordination»,  «Leading  Arm»,  «Compare  the  shape»,  «Mixed  up   lines»,«Recognition of figures», «What is unnecessary?», «Find a pair», «What face?»,«Sticks and dashes», «School», «Bad-good», «Profile of social development» can provide features of the intellectual, motivational, emotional and volitional, commu- icative readiness of children with hearing disorders. It has been shown that children with hearing impairment are characterized by a sufficient level of emotional and volitional readiness for school; diversity of speech readiness that is appeared at different levels of vocabulary mastering, dialogue and connected speech; secondary deviations resulting from auditory deprivation cause sensory and thinking originality; the most important are the motives associated with incidental product of learning (social motives, game motives, motives associated with the outer attributes of school life).